Conducta Obstétrica Ante Muerte fetal de 23,5 SG en pacientes Primigesta de 20 años con sobrepeso Grado II - Masapanta Masapanta, María Diocelina (2022)
The body weight of a pregnant woman is considered a complex point during this process. Since it not only affects physical changes but also a change in placental metabolism. Variation in weight is due to genetic, ethnic and sociocultural factors, according to the World Health Organization. Based on these data, it is sought to determine the different risks that a pregnant woman can have, its consequences during the gestation period, all of this through the collection of antecedents of both the patient and the circle of conditions to which she is exposed. that it is immersed. It is also detailed in this study that being overweight in a pregnant woman directly affects the developing fetus, with high and lower risk complications, these being, for example, complications for childbirth compared to a woman who carries a normal weight of pregnancy. Likewise, pregnancy in this case is affected by risks leading to the main issue since an increase in BMI during pregnancy is translated and related to complications of abnormal growth of the fetus, risks of fetal malformations, premature birth or worse of cases a fetal death.